Teachers' Reception of the Heroic Ideology of the Novel "Poor People Are Prohibited from Going to School" Based on Gender Classification - Sukma, Dimas Pramata; Supriyanto, Teguh; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Journal La Edusci, 2025)
Literary works are a depiction of human life through the outpouring of expression and thought. The ideology of heroism is one ideology that can be found in every Indonesian novel. However, there is a phenomenon of the interpretation of the ideology of heroism by teachers that is still confusing. Based on this problem, teachers are needed to be open in interpreting the ideology of heroism. The right solution is through the reception of the ideology of heroism in the novel Orang Miskin Dilarang Sekolah (Poor People Are Forbidden to Go to School). The approach of this research is the sociology of literature by adopting the research design of Moser (1989:1799-1825). The results of the reception of the ideology of heroism of SMK teachers in Tegal Regency towards the novel Orang Miskin Dilarang Sekolah by Eko Prasetyo based on gender classification show several differences. According to male teachers, heroism is interpreted in the form of love for the country, upholding unity, expertise in using knowledge as a weapon, and loyalty to principles. Meanwhile, according to female teachers, heroism appears in the form of prioritizing common interests, willingness to sacrifice, and sincerity. However, both agree that heroism also involves fighting for the rights of others and having a fighting spirit.